2016
DOI: 10.1111/febs.13699
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular granzyme K mediates endothelial activation through the cleavage of protease‐activated receptor‐1

Abstract: Granzymes are a family of serine proteases that were once thought to function exclusively as mediators of cytotoxic lymphocyte‐induced target cell death. However, non‐apoptotic roles for granzymes, including granzyme K (GzK), have been proposed. As recent studies have observed elevated levels of GzK in the plasma of patients diagnosed with clinical sepsis, we hypothesized that extracellular GzK induces a proinflammatory response in endothelial cells. In the present study, extracellular GzK proteolytically acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 61 publications
(77 reference statements)
5
59
0
Order By: Relevance
“…Because classically activated macrophages secrete GzmK (Figure 1e), we investigated the downstream effects of GzmK in vitro in human HaCaTs (keratinocytes) and primary human skin fibroblasts, the predominating cell types in skin. Addition of recombinant human GzmK (rhGzmK) to cells ( 100 nmol/L) showed no detectable cytotoxicity up to 48 hours in culture (see Supplementary Figure S2 online), as previously reported in endothelial cells (Sharma et al, 2016) and lung fibroblasts (Cooper et al, 2011). Using an electric cellsubstrate impedance sensing wound healing assay, rhGzmK exhibited a dose-dependent and reproducible impairment of wound closure in HaCaTs, which was approximately 50% slower compared with untreated controls (Figure 4a).…”
Section: Gzmk Impairs Healing Of Wounded Keratinocytessupporting
confidence: 69%
See 4 more Smart Citations
“…Because classically activated macrophages secrete GzmK (Figure 1e), we investigated the downstream effects of GzmK in vitro in human HaCaTs (keratinocytes) and primary human skin fibroblasts, the predominating cell types in skin. Addition of recombinant human GzmK (rhGzmK) to cells ( 100 nmol/L) showed no detectable cytotoxicity up to 48 hours in culture (see Supplementary Figure S2 online), as previously reported in endothelial cells (Sharma et al, 2016) and lung fibroblasts (Cooper et al, 2011). Using an electric cellsubstrate impedance sensing wound healing assay, rhGzmK exhibited a dose-dependent and reproducible impairment of wound closure in HaCaTs, which was approximately 50% slower compared with untreated controls (Figure 4a).…”
Section: Gzmk Impairs Healing Of Wounded Keratinocytessupporting
confidence: 69%
“…Proinflammatory IL-6, essential for timely wound healing, is involved in generating acute phase responses, inflammation, and lymphocyte differentiation (McFarland-Mancini et al, 2010). GzmK-mediated IL-6 secretion occurs in endothelial cells (Sharma et al, 2016), and our data showed GzmKmediated IL-6 secretion from cultured HaCaTs and skin fibroblasts, releasing similar quantities from each, and both operating through PAR-1. Indeed, in GzmK e/e mouse burns at day 3 after injury, IL-6 expression was reduced compared with equivalent WT samples.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations